Intermediate Cities and Transport Systems in Embedding Global Agendas: A Multi-Level Approach to SDG Implementation - Grazia Calabro; Fabio Carlucci; Carlotta D’Alessandro; Barbara Trincone (European Scientific Journal, ESJ, 2026)
The implementation of the Sustainable Development Goals (SDGs) has revealed a persistent gap between globally defined targets and their effective translation into territorially embedded development processes.This paper reframes the SDGs as an evolving architecture of multi-level socio-economic planning, the success of which depends on the capacity of sub-national governance systems to operationalise global goals within local economic structures. Within this framework, transport systems and mobility infrastructures emerge as critical enabling dimensions, shaping the spatial organisation of economic activity and simultaneously structuring the accessibility conditions underpinning social inclusion and service provision.Focusing on intermediate cities, the study argues that these centres consitute strategic meso-level arenas in which policy translation, institutional coordination, and place-based development processes converge. Transport networks—both physical infrastructures (road, rail, intermodal) and organisational arrangements (mobility services, logistics, regulatory frameworks)—play a pivotal role in structuring these dynamics. They function not only as spatial connectors, but also as integrative platforms linking regional production systems with global value chains, while simultaneously sustaining local accessibility.By adopting a conceptual/policy review, the analysis positions intermediate cities at European and Italian level, as key operational nodes for the delivery of global development agendas through context-sensitive planning. It concludes that the effectiveness of SDG implementation depends less on goal-setting than on the capacity to embed global agendas within territorially specific systems—an embedding process in which transport and mobility act as both catalysts and structuring elements of sustainable and inclusive development.